The Role Of Buddhist Ethics And Communication In The Contemporary World Crisis - Phramaha Pornchai Sripakdee (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
In reality, man cannot live without communication; at least, he communicates something with himself, thoughts, for instance. In order to successfully communicate something as such, ethics concerning any kinds of communication should be taken into a critical examination; what kind of speech one should speak out, what kind of speech one should not speak out. In this article, an attempt was purposely made to discuss the role of Buddhist ethics and communication in the contemporary world crisis. In this, it is argued by Buddhist ethics that the communication should be subject to ethics because of man’s ideal life, without it, such communication will pose the danger to the chance in obtaining the goal, ideal life.